the 4th term of an AP is zero. prove that the 25th term of an AP is three times its 11th term.
Answers
Answered by
2
.here,
t4 = 0
let the first term of an ap be a and the common difference be x
therefore,
t4 = 0 =a + 3x
a =-3x....1
t11=a +10x
substituting the value of a from eqn1 we get,
t11 = -3x + 10x =7 x.....2
t25 = a + 24x
using eqn1 we get,
t25 = -3x + 24x = 21x=3(7x)....3
joining eqn2 and eqn2 we get,
t25 = 3(t11)
(proved)
t4 = 0
let the first term of an ap be a and the common difference be x
therefore,
t4 = 0 =a + 3x
a =-3x....1
t11=a +10x
substituting the value of a from eqn1 we get,
t11 = -3x + 10x =7 x.....2
t25 = a + 24x
using eqn1 we get,
t25 = -3x + 24x = 21x=3(7x)....3
joining eqn2 and eqn2 we get,
t25 = 3(t11)
(proved)
Answered by
19
kindly refers to the attached file for answer.
☺
![hope \: this \: helps \: u \: dear hope \: this \: helps \: u \: dear](https://tex.z-dn.net/?f=hope+%5C%3A+this+%5C%3A+helps+%5C%3A+u+%5C%3A+dear)
✌✌✌.
☺
✌✌✌.
Attachments:
![](https://hi-static.z-dn.net/files/d29/f102a7603d39e91744af4f2afdace135.jpg)
Similar questions